FRI0199 In patients with established RA, abatacept efficacy is independent of baseline annual radiographic progression rate. (23rd January 2014) - Emery, P.; Westhovens, R.; Dougados, M.; Alten, R.; Gaillez, C.; Poncet, C.; Le Bars, M.; Elegbe, A.; Genant, H.
Abstract : Background: In the Phase III, double-blind, placebo (PBO)-controlled AIM study, abatacept (ABA)+ MTX significantly inhibited structural damage progression vs PBO+MTX in pts with established RA and inadequate response to MTX. 1 Sustained inhibition of radiographic progression was seen up to yr 5. 2 Previous data in pts with early RA showed a benefit of ABA in pts with faster progression. 3 Objectives: To assess clinical outcomes at 1 yr according to annual radiographic progression rate (ARPR) by quartile at baseline (BL) in pts with established RA in AIM. Methods: BL characteristics were similar between ABA 10 mg/kg+MTX (n=433) and PBO+MTX (n=219). ARPR was defined as total Genant-modified Sharpscore divided by disease duration. Pts were categorized into four quartiles according to ARPR at BL (Q1: ≤2.78; Q2: 2.78 to ≤4.64; Q3: 4.64 to ≤8.04; Q4: >8.04). For each quartile, treatment benefit was assessed post hoc by outcomes: DAS28(CRP)-derived criteria (remission <2.6; LDAS ≤3.2), Simplified Disease Activity Index Low Disease Activity (SDAI ≤11) and ACR50 response. Results: Mean (SD) BL ARPR was 8.13 (18.11) for ABA+MTX and 5.87 (5.36) for PBO+MTX. For ABA+MTX vs PBO+MTX, the percentage of pts achieving an outcome at yr 1 by ARPR quartile is shown, with treatment differences (table ). 95% CI of ABA vs PBO estimate of treatment difference did not cross zero for most ARPR quartiles. For LDAS (assessed by DAS28[CRP] or SDAI) and ACR50, there was a numerically higher treatment difference for pts in some of the higher quartiles (Q3/Q4). Conclusions: Over 1 yr, pts with established RA achieved better outcomes with abatacept +MTX than PBO+MTX across all quartiles. Pts with rapid radiographic progression (Q4) showed numerically greater clinical benefits in LDAS, SDAI and ACR50 compared with Q1 pts, extending previous findings in early RA. 3 References: Kremer J et al. Ann Intern Med 2006;144:865–76. Schiff M. Rheum 2011;50:437–49. Westhovens R et al. Ann Rheum Dis2011;70(Suppl 3):617. Disclosure of Interest: P. Emery Grant/Research support from: Abbott Immunology Pharmaceuticals, Abbott Laboratories, BMS, Centocor Research and Development, Inc., Merck Pharmaceuticals, Pfizer Inc, Roche, UCB, Inc., Consultant for: Abbott Laboratories, Amgen Inc., BMS, Centocor Research and Development, Inc., Lilly USA, LLC., Merck Pharmaceuticals, Pfizer Inc, Roche, Schering-Plough, Takeda Pharmaceuticals North America, Wyeth Pharmaceuticals, UCB, Inc., Speakers Bureau: Abbott Immunology Pharmaceuticals, BMS, Centocor Research and Development, Inc., Merck Pharmaceuticals, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, UCB, Inc., R. Westhovens Grant/Research support from: Roche, UCB, Consultant for: Bristol-Myers Squibb, Centocor, Roche, Schering-Plough, Speakers Bureau: Bristol-Myers Squibb, M. Dougados Grant/Research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, R. Alten Grant/Research support from: BMS, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers Bureau: Abbott Laboratories, BMS, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, C. Gaillez Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Poncet: None Declared, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Elegbe Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, H. Genant Shareholder of: Synarc, Inc., Grant/Research support from: Bristol-Myers Squibb, GSK, Roche, Genentech, Pfizer, Consultant for: Bristol-Myers Squibb, GSK, Roche, Genentech, Amgen, Merck, Servier, Pfizer, Lilly, Employee of: Synarc, Inc.